The constitutional roles of local governments in Nigeria: issues and challenges - Saulawa, Mu’azu Abdullahi; Danjuma, Ibrahim; Musa, Kabir Umar; Haruna, Haruna Muhammad (2016)
The paper focuses on the constitutional roles of local governments in Nigeria: issues and challenges.The creation of local governments in Nigeria is meant to support the locals on their budding future in a platform purposely created for representation in the political administration of a State and the Federal Government.The aim of the paper is to discuss the roles of local governments as provided by the 1999 Constitution of the federal Republic of Nigeria, as amended 2011. In addition, to examine the laws of the local governments and further analyses the loopholes in the legal relations between the Local Governments in Nigeria and the States.The methodology adopted by the paper is content analysis approach wherein related literatures were discussed and analysed, particularly the local laws and other relevant documents.The findings of the paper reveal that firm control of local governments by the States especially through the Joint Accounts negates the developmental purposes of local government’s creation in Nigeria. In view of this, therefore, the paper suggests that for the realisation of the ultimate purpose of creation and maintaining the system, the silent constitutional lacuna of local government’s autonomy and other related issues highlighted in the paper should be address.